2009
DOI: 10.1007/s11605-009-0999-z
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic and Parasympathetic Regulation of Rectal Motility in Rats

Abstract: Rectal motility is significantly altered by sectioning or stimulating either HGN or PN. This model may be useful in studying how sacral nerve stimulation exerts its effects and provide insight into the maladies of colonic motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…30 Our results also correspond to findings in dogs, where damage to PN branches slowed down colonic transit, inhibited defecation reflex, 9 and resulted in diminished electrical activity. 35 To our knowledge, this is the first demonstration in guinea pigs that actual changes are observed in colonic pellet propagation velocity in response to PN or IMG stimulation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…30 Our results also correspond to findings in dogs, where damage to PN branches slowed down colonic transit, inhibited defecation reflex, 9 and resulted in diminished electrical activity. 35 To our knowledge, this is the first demonstration in guinea pigs that actual changes are observed in colonic pellet propagation velocity in response to PN or IMG stimulation.…”
Section: Discussionsupporting
confidence: 89%
“…Our laboratory has produced a number of studies in a rat model, demonstrating that transection of parasympathetic PN significantly delayed colonic transit time, while the transection of sympathetic hypogastric nerve significantly increased colonic motility. 30 Response to parasympathetic nerve stimulation was abolished by muscarinic receptor blockade, while response to sympathetic nerve stimulation was abolished by beta-adrenoreceptor blockade. 31 We also showed that the PN dissection significantly impaired colonic transit and colonic motility in rats.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…8,37,38 Compensatory mechanisms occur after ANS denervation in order to reestablish intestinal function under a variety of conditions and include (1) an upregulation of gastrointestinal (GI) receptor expression, (2) compensation by the nondenervated ANS branch and (3) enteric nervous system modulation. For example, PNS denervation initially decreases intestinal motility, 39 a process which is heavily mediated by serotonin. 40 PNS denervation has also been shown to reduce the amount of 5-HT-3 positive serotonergic nerve fibers in the GI tract.…”
Section: Discussionmentioning
confidence: 99%